Enabling End-User for LV Smart Grids - Faranda, R.; Akkala, N. V. K.; Hafezi, H. (IEEE, 2019)
In order to increase the rate of transformation of traditional grid to a future Smart Grid, there is a huge necessity for enabling the end-user to become an activity participant. Technological and financial considerations are key driving factors in empowering the end-user. From a technological point of view end-user needs to manage his own load, power generated from renewables and also in providing the services to the grid. A promising and innovative solution to meet these needs of the end user in LV network is the Open UPQC (Open Unified Power Quality Conditioner). This device has been designed to meet different tasks required by an end-user (Power Quality, Demand Response, Ancillary Service, etc.). This paper presents the Shunt Unit of Open UPQC with RES (Renewable Energy Sources) as a solution which can provide all the necessary functionalities required by an end-user in enabling him to become an active participant in electrical grid transformation. The performance of the device is demonstrated using simulation results under online and island operation modes.
Keywords: End-User; Open UPQC; renewable energy; Shunt Unit; Smart grid; end users; smart grids; fi=Sähkötekniikka|en=Electrical Engineering|